Auxin: an emerging regulator of tuber and storage root development - Kondhare, Kirtikumar R.; Patil, Aruna B.; Giri, Ashok P. (Plant Science, 2021)
Many tuber and storage root crops owing to their high nutritional values offer high potential to overcome food security issues. The lack of information regarding molecular mechanisms that govern belowground storage organ development (except a tuber crop, potato) has limited the application of biotechnological strategies for improving storage crop yield. Phytohormones like gibberellin and cytokinin are known to play a crucial role in governing potato tuber development. Another phytohormone, auxin has been shown to induce tuber initiation and growth, and its crosstalk with gibberellin and strigolactone in a belowground modified stem (stolon) contributes to the overall potato tuber yield. In this review, we describe the crucial role of auxin biology in development of potato tubers. Considering the emerging reports from commercially important storage root crops (sweet potato, cassava, carrot, sugar beet and radish), we propose the function of auxin and related gene regulatory network in storage root development. The pattern of auxin content of stolon during various stages of potato tuber formation appears to be consistent with its level in various developmental stages of storage roots. We have also put-forward the potential of three-way interaction between auxin, strigolactone and mycorrhizal fungi in tuber and storage root development. Overall, we propose that auxin gene regulatory network and its crosstalk with other phytohormones in stolons/roots could govern belowground tuber and storage root development.
Keywords: Auxin; Potato; Storage root; Sweet potato; Tuber

Development of aerial and belowground tubers in potato is governed by photoperiod and epigenetic mechanism - Kondhare, Kirtikumar R.; Kumar, Amit; Patil, Nikita S.; Malankar, Nilam N.; Saha, Kishan; Banerjee, Anjan K. (Plant Physiology, 2021)
Plants exhibit diverse developmental plasticity and modulate growth responses under various environmental conditions. Potato (Solanum tuberosum), a modified stem and an important food crop, serves as a substantial portion of the world's subsistence food supply. In the past two decades, crucial molecular signals have been identified that govern the tuberization (potato development) mechanism. Interestingly, microRNA156 overexpression in potato provided the first evidence for induction of profuse aerial stolons and tubers from axillary meristems under short-day (SD) photoperiod. A similar phenotype was noticed for overexpression of epigenetic modifiers-MUTICOPY SUPRESSOR OF IRA1 (StMSI1) or ENAHNCER OF ZESTE 2 (StE[z]2), and knockdown of B-CELL-SPECIFIC MOLONEY MURINE LEUKEMIA VIRUS INTEGRATION SITE 1 (StBMI1). This striking phenotype represents a classic example of modulation of plant architecture and developmental plasticity. Differentiation of a stolon to a tuber or a shoot under in vitro or in vivo conditions symbolizes another example of organ-level plasticity and dual fate acquisition in potato. Stolon-to-tuber transition is governed by SD photoperiod, mobile RNAs/proteins, phytohormones, a plethora of small RNAs and their targets. Recent studies show that polycomb group proteins control microRNA156, phytohormone metabolism/transport/signaling and key tuberization genes through histone modifications to govern tuber development. Our comparative analysis of differentially expressed genes between the overexpression lines of StMSI1, StBEL5 (BEL1-LIKE transcription factor [TF]), and POTATO HOMEOBOX 15 TF revealed more than 1,000 common genes, indicative of a mutual gene regulatory network potentially involved in the formation of aerial and belowground tubers. In this review, in addition to key tuberization factors, we highlight the role of photoperiod and epigenetic mechanism that regulates the development of aerial and belowground tubers in potato.

Diversity in chemical structures and biological properties of plant alkaloids - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Molecules, 2021)
Phytochemicals belonging to the group of alkaloids are signature specialized metabolites endowed with countless biological activities. Plants are armored with these naturally produced nitrogenous compounds to combat numerous challenging environmental stress conditions. Traditional and modern healthcare systems have harnessed the potential of these organic compounds for the treatment of many ailments. Various chemical entities (functional groups) attached to the central moiety are responsible for their diverse range of biological properties. The development of the characterization of these plant metabolites and the enzymes involved in their biosynthesis is of an utmost priority to deliver enhanced advantages in terms of biological properties and productivity. Further, the incorporation of whole/partial metabolic pathways in the heterologous system and/or the overexpression of biosynthetic steps in homologous systems have both become alternative and lucrative methods over chemical synthesis in recent times. Moreover, in-depth research on alkaloid biosynthetic pathways has revealed numerous chemical modifications that occur during alkaloidal conversions. These chemical reactions involve glycosylation, acylation, reduction, oxidation, and methylation steps, and they are usually responsible for conferring the biological activities possessed by alkaloids. In this review, we aim to discuss the alkaloidal group of plant specialized metabolites and their brief classification covering major categories. We also emphasize the diversity in the basic structures of plant alkaloids arising through enzymatically catalyzed structural modifications in certain plant species, as well as their emerging diverse biological activities. The role of alkaloids in plant defense and their mechanisms of action are also briefly discussed. Moreover, the commercial utilization of plant alkaloids in the marketplace displaying various applications has been enumerated.
Keywords: alkaloid; Biological activity; classification; defense; Enzyme; modification

Historical overview of long-distance signalling in plants - Kondhare, Kirtikumar R.; Patil, Nikita S.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Be it a small herb or a large tree, intra- and intercellular communication and long-distance signalling between distant organs are crucial for every aspect of plant development. The vascular system, comprising xylem and phloem, acts as a major conduit for the transmission of long-distance signals in plants. In addition to expanding our knowledge of vascular development, numerous reports in the past two decades revealed that selective populations of RNAs, proteins, and phytohormones function as mobile signals. Many of these signals were shown to regulate diverse physiological processes, such as flowering, leaf and root development, nutrient acquisition, crop yield, and biotic/abiotic stress responses. In this review, we summarize the significant discoveries made in the past 25 years, with emphasis on key mobile signalling molecules (mRNAs, proteins including RNA-binding proteins, and small RNAs) that have revolutionized our understanding of how plants integrate various intrinsic and external cues in orchestrating growth and development. Additionally, we provide detailed insights on the emerging molecular mechanisms that might control the selective trafficking and delivery of phloem-mobile RNAs to target tissues. We also highlight the cross-kingdom movement of mobile signals during plant-parasite relationships. Considering the dynamic functions of these signals, their implications in crop improvement are also discussed.
Keywords: Long-distance signalling; mobile RNAs; phloem; plasmodesmata; RNA-binding proteins; small RNAs

Polycomb group methyltransferase StE(z)2 and deposition of H3K27me3 and H3K4me3 regulate the expression of tuberization genes in potato - Kumar, Amit; Kondhare, Kirtikumar R.; Malankar, Nilam N.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Polycomb repressive complex (PRC) group proteins regulate various developmental processes in plants by repressing target genes via H3K27 trimethylation, and they function antagonistically with H3K4 trimethylation mediated by Trithorax group proteins. Tuberization in potato has been widely studied, but the role of histone modifications in this process is unknown. Recently, we showed that overexpression of StMSI1, a PRC2 member, alters the expression of tuberization genes in potato. As MSI1 lacks histone-modification activity, we hypothesized that this altered expression could be caused by another PRC2 member, StE(z)2, a potential H3K27 methyltransferase in potato. Here, we demonstrate that a short-day photoperiod influences StE(z)2 expression in the leaves and stolons. StE(z)2 overexpression alters plant architecture and reduces tuber yield, whereas its knockdown enhances yield. ChIP-sequencing using stolons induced by short-days indicated that several genes related to tuberization and phytohormones, such as StBEL5/11/29, StSWEET11B, StGA2OX1, and StPIN1 carry H3K4me3 or H3K27me3 marks and/or are StE(z)2 targets. Interestingly, we observed that another important tuberization gene, StSP6A, is targeted by StE(z)2 in leaves and that it has increased deposition of H3K27me3 under long-day (non-induced) conditions compared to short days. Overall, our results show that StE(z)2 and deposition of H3K27me3 and/or H3K4me3 marks might regulate the expression of key tuberization genes in potato.
Keywords: ChIP-sequencing; Epigenetics; PcG; photoperiod; polycomb repressive complex; potato tuberization; short-day; Solanum tuberosum; StE(z)2

Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites

Ocimum kilimandscharicum 4CL11 negatively regulates adventitious root development via accumulation of flavonoid glycosides - Lavhale, Santosh G.; Kondhare, Kirtikumar R.; Sinthadurai, Veenothini S.; Barvkar, Vitthal T.; Kale, Rutuja S.; Joshi, Rakesh S.; Giri, Ashok P. (Plant Journal, 2024)
4-Coumarate-CoA Ligase (4CL) is an important enzyme in the phenylpropanoid biosynthesis pathway. Multiple 4CLs are identified in Ocimum species; however, their in planta functions remain enigmatic. In this study, we independently overexpressed three Ok4CL isoforms from Ocimum kilimandscharicum (Ok4CL7, -11, and -15) in Nicotiana benthamiana. Interestingly, Ok4CL11 overexpression (OE) caused a rootless or reduced root growth phenotype, whereas overexpression of Ok4CL15 produced normal adventitious root (AR) growth. Ok4CL11 overexpression in N. benthamiana resulted in upregulation of genes involved in flavonoid biosynthesis and associated glycosyltransferases accompanied by accumulation of specific flavonoid-glycosides (kaempferol-3-rhamnoside, kaempferol-3,7-O-bis-alpha-l-rhamnoside [K3,7R], and quercetin-3-O-rutinoside) that possibly reduced auxin levels in plants, and such effects were not seen for Ok4CL7 and -15. Docking analysis suggested that auxin transporters (PINs/LAXs) have higher binding affinity to these specific flavonoid-glycosides, and thus could disrupt auxin transport/signaling, which cumulatively resulted in a rootless phenotype. Reduced auxin levels, increased K3,7R in the middle and basal stem sections, and grafting experiments (intra and inter-species) indicated a disruption of auxin transport by K3,7R and its negative effect on AR development. Supplementation of flavonoids and the specific glycosides accumulated by Ok4CL11-OE to the wild-type N. benthamiana explants delayed the AR emergence and also inhibited AR growth. While overexpression of all three Ok4CLs increased lignin accumulation, flavonoids, and their specific glycosides were accumulated only in Ok4CL11-OE lines. In summary, our study reveals unique indirect function of Ok4CL11 to increase specific flavonoids and their glycosides, which are negative regulators of root growth, likely involved in inhibition of auxin transport and signaling.
Keywords: 4-Coumarate-CoA ligase; 7-O-bis-alpha-l-rhamnoside; adventitious root; auxin transport; Flavonoids; kaempferol-3; Ocimum kilimandscharicum; quercetin-3-O-rutinoside; rootless

Mobile RNAs and proteins: impacts on plant growth and productivity - Kondhare, Kirtikumar R.; Bhide, Amey J.; Banerjee, Anjan K. (Journal of Experimental Botany, 2025)
Short- and long-distance mobile signals (mobile RNAs and proteins) are integral parts of the local and systemic communications that coordinate various physiological processes at the whole-plant level and have far-reaching impacts on plant productivity. In this review, we aim to provide a comprehensive description of the integral roles of these mobile signals in controlling phenotypic traits and plant productivity. We describe how key mobile RNAs (mRNAs, small RNAs, and long non-coding RNAs) and proteins (including RNA-binding proteins) function as vital regulators of multi-faceted aspects of phenotypic traits that ultimately govern plant productivity, such as the formation of the shoot apical meristem, leaf morphology, root architecture, flowering, ripening of fleshy fruits, tuberization, crop yield, and abiotic stress responses. We also describe recent advances in the study of macromolecular transport mechanisms, such as cyclophilin-mediated transport and extracellular vesicle-based signal delivery, as well as the identification of novel signature motifs on mobile RNAs. In addition, we consider the discovery of new mobile signals and highlight how these signals can potentially be explored with advanced biotechnological interventions, virus-induced flowering, genome-editing tools, and emerging breeding approaches (e.g. the xenia-based mobile RNA delivery system for fleshy fruits) with the aim of designing strategies for enhancing valuable phenotypic traits and improving plant productivity. Mobile RNAs and proteins act as key regulators of shoot apical meristem development, leaf morphology, root architecture, flowering, fleshy fruit ripening, tuberization, yield, and responses to abiotic stresses in plants.
Keywords: Long non-coding RNA; mobile protein; mobile RNA; plant productivity; RNA-binding protein; small RNA

MYB proteins: Versatile regulators of plant development, stress responses, and secondary metabolite biosynthetic pathways - Bhatt, Preshita A.; Gurav, Tanuja P.; Kondhare, Kirtikumar R.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2025)
MYB proteins are ubiquitous in nature, regulating key aspects of plant growth and development. Although MYB proteins are known for regulating genes involved in secondary metabolite biosynthesis, particularly phenylpropanoids, their roles in terpenoid, glucosinolate, and alkaloid biosynthesis remain less understood. This review explores the structural and functional differences between activator and repressor MYB proteins along with their roles in plant growth, development, stress responses, and secondary metabolite production. MYB proteins serve as central hubs in protein-protein interaction networks that regulate expression of numerous genes involved in the adaptation of plants to varying environmental conditions. Thus, we also highlight key interacting partners of MYB proteins and their roles in these adaptation mechanisms. We further discuss the mechanisms regulating MYB proteins, including autoregulation, epigenetics, and post-transcriptional and post-translational modifications. Overall, we propose MYB proteins as versatile regulators for improving plant traits, stress responses, and secondary metabolite production.
Keywords: Activator; defense; Development; MYB protein; Repressor; Secondary metabolites

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics

Rootless survivors in plants - Kondhare, Kirtikumar R.; Lavhale, Santosh G.; Giri, Ashok P. (Plant Science, 2026)
The root system provides anchorage, uptakes of nutrients and water, and forms different associations within soil environments that govern plant fitness, crop performance, and yield. Auxin controls almost all aspects of root development. Both shoot- and root-derived auxins contribute to formation of polar auxin transport, which is crucial for establishing and maintaining normal root architecture. The coordinated activities of auxin influx and efflux carriers establish necessary polar auxin transport. A variety of natural metabolites and synthetic compounds are shown to interfere with auxin metabolism, transporters and signaling pathways having a negative impact on root growth. In this review, we highlight the reports demonstrating the observance of rootless phenotypes in plants and associated molecular mechanisms. Rootless phenotypes can be produced under in vitro culture conditions by modulation of phytohormone combinations (especially auxin and cytokinin), and supplementation of naturally-occurring flavonoids and their glycosides or synthetic auxin transport inhibitors (1-Nnaphthylphthalamic acid and 2,3,5-triiodobenzoic acid) or under in vivo conditions by modulation of several genes directly or indirectly associated with auxin biology. Further, we describe the crosstalk of naturallyoccurring flavonoids (e.g. kaempferol, quercetin), their glycosides, and other metabolites (e.g. azelaic acid, cis-cinnamic acid) with auxin transporters, their mobile nature, and influence on root development. Moreover, we provide evolutionary perspective on the auxin and flavonoid pathways and their possible roles in naturally rootless plants. We also emphasize the importance of rootless or reduced root growth phenotypes in modern agriculture, and the pressing needs to utilize naturally occurring auxin transport inhibitors for industrial and research applications.
Keywords: Auxin; Flavonoid; Flavonoid-glycoside; Polar auxin transport; rootless